2018
DOI: 10.1080/14767058.2018.1506443
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction associated with paternal isodisomy of chromosome 5: a clinical report and literature survey

Abstract: The present case supports the reports that genes on chromosome 5 are nonimprinted. The implications of abnormal genetic findings on genetic counseling are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Moreover, we identified unconventional heterogeneous genetic etiologies for FNIP1 deficiency in two patients, expanding the variant spectrum of this novel inborn error of immunity (IEI; supplemental Figure 10A). In fact, only a limited number of cases of chromosome 5 UPD have been reported 16 . Our findings argue for the clinical use of exome sequencing with copy number variants analysis in patients with complex phenotypes.…”
Section: Fnip1 Deficiency Is Associated With Altered Cell Metabolismmentioning
confidence: 99%
“…Moreover, we identified unconventional heterogeneous genetic etiologies for FNIP1 deficiency in two patients, expanding the variant spectrum of this novel inborn error of immunity (IEI; supplemental Figure 10A). In fact, only a limited number of cases of chromosome 5 UPD have been reported 16 . Our findings argue for the clinical use of exome sequencing with copy number variants analysis in patients with complex phenotypes.…”
Section: Fnip1 Deficiency Is Associated With Altered Cell Metabolismmentioning
confidence: 99%
“…To date, more studies have shown that UPD will result in FGR (22)(23)(24). Our study identified a loss of heterozygosity in the 14q13.2q21.3 region who exhibit FGR combined with ventricular septal defect, auricle abnormality and hypoxia.…”
Section: Discussionmentioning
confidence: 58%